The Mixed Fleet Hybrid Truck Platoon Network Design Problem - Ioannou, I. P.; Liatsos, V.; Kaisar, E.; Golias, Mihalis (My University, 2024)
In recent years, the concept of truck platooning has garnered significant attention within the transportation community. In this paper we build upon the formulation of the hybrid truck platoon network design problem, initially proposed by Liatsos et al., (2023, 2024), by introducing a mixed fleet of combustion and electric trucks where both vehicle types are available for to form platoons. Central to the proposed model is an exploration of the impact of various operational conditions on potential monetary savings and the reliability of the supply chain network. These operational conditions include factors such as platoon size dependent travel time, variable platoon capacity, arrival time deadlines, and willingness to wait at platoon coupling-decoupling points for recharging.
Keywords: Truck Platooning; Combustion Engine; Electric Vehicles; Network Design; Cost Savings